A tomato NAC transcription factor, SlNAM1, positively regulates ethylene biosynthesis and the onset of tomato fruit ripening. (2nd November 2021) - Gao, Ying; Fan, Zhong‐Qi; Zhang, Qiang; Li, Hong‐Li; Liu, Gang‐Shuai; Jing, Yuan; Zhang, Yi‐Ping; Zhu, Ben‐Zhong; Zhu, Hong‐Liang; Chen, Jian‐Ye; Grierson, Donald; Luo, Yun‐Bo; et al.
SUMMARY: Fruit ripening in tomato ( Solanum lycopersicum ) is the result of selective expression of ripening‐related genes, which are regulated by transcription factors (TFs). The NAC (NAM, ATAF1/2, and CUC2) TF family is one of the largest families of plant‐specific TFs and members are involved in a variety of plant physiological activities, including fruit ripening. Fruit ripening‐associated NAC TFs studied in tomato to date include NAC‐NOR (non‐ripening), SlNOR‐like1 (non‐ripening like1), SlNAC1, and SlNAC4. Considering the large number of NAC genes in the tomato genome, there is little information about the possible roles of other NAC members in fruit ripening, and research on their target genes is lacking. In this study, we characterize SlNAM1, a NAC TF, which positively regulates the initiation of tomato fruit ripening via its regulation of ethylene biosynthesis. The onset of fruit ripening in slnam1 ‐deficient mutants created by CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats and CRISPR‐associated protein 9) technology was delayed, whereas fruit ripening in OE ‐SlNAM1 lines was accelerated compared with the wild type. The results of RNA‐sequencing (RNA‐seq) and promoter analysis suggested that SlNAM1 directly binds to the promoters of two key ethylene biosynthesis genes (1‐aminocyclopropane‐1‐carboxylate synthase: SlACS2 and SlACS4 ) and activates their expression. This hypothesis was confirmed by electrophoretic mobility shift assays and dual‐luciferase reporter assay. Our findings provide insights into the mechanisms of ethylene production and enrich understanding of the tomato fruit ripening regulatory network. Significance Statement: System II ethylene synthesis was regulated by transcription factors to start climacteric fruit ripening. Previously reported ripening‐related NAC transcription factors regulate the final ripening of tomato fruit by affecting the peak of system II ethylene. In this study, we found that the mutation and overexpression of SlNAM1 regulated the initiation of fruit ripening and did not affect the ethylene peak and final ripening in tomato. The result enriches the theory of NAC regulating fruit ripening.